Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12890-023-02677-0
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MRPL35 promotes cell apoptosis and inhibits cell proliferation in non-small-cell lung cancer

Chengling Zhao,
Lei Chen,
Zhixin Jin
et al.

Abstract: Background Non-small cell lung cancer (NSCLC) is a major pathological type of lung cancer. However, its pathogenesis remains largely unclear. MRPL35 is a regulatory subunit of the mitoribosome, which can regulate the assembly of cytochrome c oxidases and plays an important role in the occurrence of NSCLC. Methods The expression of MRPL35 in NSCLC was detected by tissue microarray and immunohistochemistry. H1299 cells were infected with lentivirus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…In our study, a high expression of MRPL35 in NSCLC patients was observed, and MRPL35 indicated poor prognosis in patients. Functionally, MRPL35 deficiency repressed NSCLC growth in vitro and in vivo, which was consistent with previous findings [ 16 ]. Moreover, we also found that MRPL35 silencing impaired cell invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, a high expression of MRPL35 in NSCLC patients was observed, and MRPL35 indicated poor prognosis in patients. Functionally, MRPL35 deficiency repressed NSCLC growth in vitro and in vivo, which was consistent with previous findings [ 16 ]. Moreover, we also found that MRPL35 silencing impaired cell invasion.…”
Section: Discussionsupporting
confidence: 92%
“…MRPL35 silencing promoted ROS‐induced autophagy and apoptosis and suppressed growth in colorectal cancer [ 15 ]. Moreover, MRPL35 suppressed the growth of NSCLC by repressing proliferation‐ and apoptosis‐related genes [ 16 ]. However, the role and mechanism of MRPL35 on glutamine metabolism in NSCLC are still vague.…”
Section: Introductionmentioning
confidence: 99%